歯科インプラントに関するアンケート調査 - 萩原, 芳幸; 小泉, 政幸; 村松, 透; 五十嵐, 孝義; 檜山, 礼秀 (Journal of Japanese Society of Oral Implantology, 1999)
The frequency of use of dental implants has been increasing in clinical practice in accordance with the development of popularity of osseointegration. It is possible to obtain a lot of information on implants from various journals and textbooks. However, only a few reports have been made on the actual situation of implant treatment in real clinical practice. Therefore, a questionnaire survey was conducted to investigate the actual situation of implant applications including examination, diagnosis, system used, surgical procedure, prosthodontics, and maintenance, the methods used in implant clinical practice. Questionnaires were sent to 600 dentists who actually do implant practice from the members of the Japan Society of Oral Implantology as subjects. The dentists were requested to fill out the questionnaine and return it. Three hundred seven questionnaire from were returned, a response rate of 51.2%. A questionnaire survey was conducted to investigate the actual situation of clinical application of implants in Japan. This survey enabled meaningful in understanding the tendency of clinical practice of using implants. Due to the results, it is expected that use of implants will be established as a safer and more predictable treatment method.